2002
DOI: 10.1016/s1381-1169(02)00062-6
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium complexes with N-phenyl anthranilic acid ligands as catalysts for hydrogenation

Abstract: The complexes of rhodium with N-phenyl anthranilic acid and anthranilic acid were synthesised and their structure was investigated with infrared spectroscopy. It appears that rhodium interacts with N-phenyl anthranilic acid via the carboxyl and the amine groups. With anthranilic acid, the bond with the amine could not be unambiguously established. X-ray diffraction and elemental analysis data suggest that the complexes are not pure and that the presence of Rh (0) is likely. Catalytic hydrogenation results and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…An additional broad feature observed in these patterns at 2y B 51 was due to the silicone-based matrix used during the sample preparation. 26 This is in direct contrast to previous CHFS works, which resulted in a mixture of VO 2 phases and required heat treatment to 600 1C to produce the phase-pure VO 2 (M). 18 It is suggested that the higher reaction temperature (ca.…”
Section: Continuous Hydrothermal Flow Synthesis and Characterisationmentioning
confidence: 80%
“…An additional broad feature observed in these patterns at 2y B 51 was due to the silicone-based matrix used during the sample preparation. 26 This is in direct contrast to previous CHFS works, which resulted in a mixture of VO 2 phases and required heat treatment to 600 1C to produce the phase-pure VO 2 (M). 18 It is suggested that the higher reaction temperature (ca.…”
Section: Continuous Hydrothermal Flow Synthesis and Characterisationmentioning
confidence: 80%
“…NPA can also bind either through one carboxylate O atom, as in the motif Zn(Hdmpz) 2 (L 2 ) 2 (Hdmpz is 3,5-dimethylpyrazole and L 2 is N-phenylanthranilate), or through both carboxylate O atoms, as in the dinuclear motif [Cu 2 (C 6 H 5 NHC 6 H 4 COO) 4 (CH 3 CH 2 OH) 2 ] (Jin & Wang, 2014;Tas ¸et al, 2010). NPA ligands were reported to coordinate to rhodium for synthesizing hydrogenation catalysts, as seen in RhPAA (PAA is N-phenylanthranilic acid) (Ros et al, 2002). Here, NPA was found to interact with the rhodium center via both the amine and carboxyl groups.…”
Section: Introductionmentioning
confidence: 97%
“…NPA is reported to act as a chelating ligand for metals, with potential for coordination through both the N atom of the amino group (N) and the O atoms of the carboxyl group (-COO À ) (Ros et al, 2002). NPA can also bind either through one carboxylate O atom, as in the motif Zn(Hdmpz) 2 (L 2 ) 2 (Hdmpz is 3,5-dimethylpyrazole and L 2 is N-phenylanthranilate), or through both carboxylate O atoms, as in the dinuclear motif [Cu 2 (C 6 H 5 NHC 6 H 4 COO) 4 (CH 3 CH 2 OH) 2 ] (Jin & Wang, 2014;Tas ¸et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mixed-ligand complexes included anthranilic acid can inhibit the DNA interactions, and cytotoxicity [4]. The literature survey show that the complexes of rhodium with anthranilic acid and N-phenyl anthranilic acid can act as catalysts for hydrogenation [5], terbium(III) complexes of anthranilic acid can appear the photoluminescence properties [6], a model into a peroxidase inhibitor complex [7]. The complexes of metals ion with two differences kinds of bioligands, as a hetero-aromatic nitrogen bases may be present the importing biochemical interactions in different ways [8].…”
Section: Introductionmentioning
confidence: 99%